2022
DOI: 10.1155/2022/4692054
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Finite Element Study on 7A04 Aluminum Alloy Tube Confined High Strength Concrete Long Column

Abstract: 7A04 aluminum alloy has high strength and strong corrosion resistance, and its quality is only 1/3 of steel. Using 7A04 aluminum alloy to replace ordinary steel tube to confined concrete, it can effectively reduce the member section, reduce the weight of the structure, and more in line with the material requirements of large span materials and high-rise buildings. In this paper, nine groups of 7A04 aluminum alloy tube confined high strength concrete long column were tested under axial compression and eccentric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The mechanical behaviors of concrete filled aluminum tubular (CFAT) columns are anticipated to be comparable to those of CFST columns owing to similar Poisson's ratio of steel and aluminum, and the presence of aluminum tube may result in an attractive look with low maintenance. There are studies conducted to explore the performance of CFAT under axial compression 38,53,58,63 . Various studies revealed that the ductility of the composite column declines with increase in core concrete's strength.…”
Section: Materials For Cft Columnsmentioning
confidence: 99%
“…The mechanical behaviors of concrete filled aluminum tubular (CFAT) columns are anticipated to be comparable to those of CFST columns owing to similar Poisson's ratio of steel and aluminum, and the presence of aluminum tube may result in an attractive look with low maintenance. There are studies conducted to explore the performance of CFAT under axial compression 38,53,58,63 . Various studies revealed that the ductility of the composite column declines with increase in core concrete's strength.…”
Section: Materials For Cft Columnsmentioning
confidence: 99%